Vertical collapse origin of Las Cañadas caldera (Tenerife, Canary Islands) revealed by 3‐D magnetotelluric inversion. Issue 6 (23rd March 2015) - Piña‐Varas, P.; Ledo, J.; Queralt, P.; Marcuello, A.; Bellmunt, F.; Ogaya, X.; Pérez, N.; Rodriguez‐Losada, J. A.
Abstract: Tenerife island geology is one of the most complexes of the Canaries archipelago. This complexity is evidenced by the existing controversy regarding the lateral or vertical collapse origin of the Las Cañadas caldera. The resistivity structure of the Las Cañadas caldera has been determined by the 3‐D inversion of 188 broadband magnetotelluric data. The resistivity distribution obtained in the final model shows clear evidences of the presence of a vertical structure under the Teide, associated to the buried northern wall of the caldera. Additionally, the characteristics of the main resistivity structure, a ring‐shaped low‐resistivity body (<10 Ω m) interpreted as a hydrothermal clay alteration cap, would point out the presence of a handwall for the Icod Valley lateral landslide located under the Teide, but not in the southern caldera wall (current wall). All these support the vertical collapse hypothesis to explain the origin of the Las Cañadas caldera. Key Points: Understanding the origin of Las Cañadas caldera by 3‐D MT inversion Role of the hydrothermal alteration in the Las Cañadas caldera formation New 3‐D inversion resistivity model of Tenerife Island